2009
DOI: 10.1037/a0015111
|View full text |Cite
|
Sign up to set email alerts
|

Spanish–English bilingual psychotherapists: Personal and professional language development and use.

Abstract: The rapid rise of the Spanish-speaking population in the United States has resulted in an increased demand for Spanish language mental health services. Yet little is known about the training needs of practitioners who provide those services. This qualitative study used in-depth telephone interviews to examine the experiences of 13 Spanish-English bilingual therapists, both native Spanish speakers and heritage speakers of Spanish, in their personal and professional language development and use. The phenomenolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
104
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 54 publications
(122 citation statements)
references
References 46 publications
17
104
0
1
Order By: Relevance
“…This is consistent with the experiences of therapists in Verdinelli and Biever (2009). These therapists did engage in code-switching (CS), but only 2 of the 13 participants had learned formally about CS.…”
Section: Language Gap and Switchingsupporting
confidence: 69%
See 4 more Smart Citations
“…This is consistent with the experiences of therapists in Verdinelli and Biever (2009). These therapists did engage in code-switching (CS), but only 2 of the 13 participants had learned formally about CS.…”
Section: Language Gap and Switchingsupporting
confidence: 69%
“…The therapists also believed that, although there were concerns about possible collusion, the benefits were that they were able to help clients to feel more connected and less isolated. Similar views emerged from Verdinelli and Biever's (2009) research with 13 SpanishEnglish bilingual psychotherapists. The psychotherapists reported that they felt more connected to clients with whom they shared their native language (L1) and that this had a positive effect on the therapy.…”
Section: Themes Emerging From the Review Of The Literaturementioning
confidence: 55%
See 3 more Smart Citations